2021
DOI: 10.1038/s41598-020-80191-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in size and shape of toxin glands among cane toads from native-range and invasive populations

Abstract: If optimal investment in anti-predator defences depends on predation risk, invading new regions (and thus, encountering different predators) may favour shifts in that investment. Cane toads offer an ideal system to test this prediction: expensive anti-predator toxins are stored mainly in parotoid glands whose dimensions are easy to measure, and toad invasions have changed the suites of predators they encounter. Although plasticity may influence parotoid morphology, comparisons between parents and progeny revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…For example, range-edge toads are more exploratory than those from the range-core [41], which may increase their likelihood of encountering predators. Parotoid glands are smaller in native-range toads than invasive Australian toads, presumably because the toxin is more effective against naive predators in introduced ranges [42]. Range-edge toads in Australia have relatively larger parotoid glands ( [43], but see [42]), which may be a response to increased predation threat to these animals or a more unpredictable predator landscape in newly colonized areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, range-edge toads are more exploratory than those from the range-core [41], which may increase their likelihood of encountering predators. Parotoid glands are smaller in native-range toads than invasive Australian toads, presumably because the toxin is more effective against naive predators in introduced ranges [42]. Range-edge toads in Australia have relatively larger parotoid glands ( [43], but see [42]), which may be a response to increased predation threat to these animals or a more unpredictable predator landscape in newly colonized areas.…”
Section: Discussionmentioning
confidence: 99%
“…Parotoid glands are smaller in native-range toads than invasive Australian toads, presumably because the toxin is more effective against naive predators in introduced ranges [42]. Range-edge toads in Australia have relatively larger parotoid glands ( [43], but see [42]), which may be a response to increased predation threat to these animals or a more unpredictable predator landscape in newly colonized areas. Fewer and potentially more predictable interactions with predators at the range-core could result in a lower cost of transmitting epigenetic marks to offspring in response to alarm cue exposure, potentially favouring intergeneration effects.…”
Section: Discussionmentioning
confidence: 99%
“…Between‐ and within‐population variation in chemical defences may reflect: (1) solely environmental conditions without any genetic effects, for example, age, local differences in nutrient availability and/or competition for resources that are necessary for the production of the chemical defence (Burdfield‐Steel et al, 2019; Speed et al, 2012); (2) genetic differences in individuals' capacity in sequestering, gathering or synthesizing compounds for chemical defence. In this case, there may be differences between sexes or we may find size‐dependent variation in chemical defence (Alonso‐Mejia & Brower, 1994; Hudson et al, 2021); or (3) that different genotypes may react differently to variable environmental conditions creating genotype‐by‐environment interactions. Evidence for the first mechanism has now been found both in species that sequester their defences (Brower et al, 1982), and in some that produce their defences themselves (i.e., de novo; Burdfield‐Steel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the toads contain a unique blend of bufadienolides in their skin secretions at each stage of their adult life. There is also a report of ontogenic and regional differences in the composition of toxins in adult toads (Hudson et al 2021). These differential compositions might cause the variation in the therapeutic properties of these toxins.…”
Section: Uplc-ms/ms Analysismentioning
confidence: 99%